Evaluation of Alcohol Screening, Brief Intervention, and Referral to Treatment (SBIRT) Training for Social Workers. Issue 1 (3rd April 2017) - Putney, Jennifer M.; O'Brien, Kimberly H. M.; Collin, Cali-Ryan; Levine, Adele
Abstract : Social work education is well positioned for workforce development initiatives that prepare practitioners to use Screening, Brief Intervention, and Referral to Treatment (SBIRT) with people at risk for alcohol use disorders. This article presents preliminary process and outcome evaluation data from the first year of a three-year grant which suggests that the training is acceptable and results in significant changes in trainees' knowledge, attitudes, and self-perceived SBIRT skills. Training was embedded within the curricula of an urban school of social work, which includes a Bachelor of Social Work (BSW) program and a single-concentration clinical Master of Social Work (MSW). Trainees included social work students ( n = 134) and field instructors ( n = 38). More than 90% of students were very satisfied or satisfied with the training, and 100% of field instructors rated the training as excellent or good. Students demonstrated significant changes from pre- to posttraining in substance use knowledge, confidence in SBIRT skills, and attitudes about integrating SBIRT into practice. Field instructors reported increased confidence in screening. Integrating SBIRT training into social work curriculum is a promising method of developing a workforce that can effectively prevent and alleviate alcohol misuse.